Towards the Non-Anthropocentric Ontology of the Educational - Chutorański, Maksymilian (INSTED: Interdisciplinary Studies in Education & Society, 2017)
The text is an attempt to develop a non-anthropocentric pedagogy of things, under which a thesis is put up on the necessity of thinking over the education implied by the anthropocentric way of thinking about what is social. By the means of references to posthumanism, social studies on science and technology and, in particular, to the theory of an actor-network, a way of thinking about the ontology of the educational was proposed, allowing to appreciate the relativity, complexity and hybridity of actors inscribed in the most basic level of (not only) educational existence.